Simultaneous determination of aflatoxins and ochratoxin A in selected spices using high performance liquid chromatography with fluorescence detector - Wan Mustapha, Wan Ainiza (2015)
Mycotoxins are found in a wide range of food making it possible for aflatoxins (AFs) and ochratoxin A (OTA) to occur simultaneously in spices and other commodities. Previously, immunoaffinity columns were designed to be used for single mycotoxin clean up and separate extractions was required if many mycotoxins were to be determined in a single food sample. Now, due to advances in technology, multi-mycotoxins immunoaffinity column were developed, making simultaneous determination possible. The objectives of this study were to develop a simultaneous determination method of AFs and OTA in selected spices, to validate the extraction procedure and to verify the method performance using curry mixture samples which were collected from retail markets. The simultaneous determination developed was a modification of a published method using multi-toxin immunoaffinity column and reverse-phased HPLC-FLD with photochemical derivatization system. Recoveries from spiked samples for AFB1, AFB2, AFG1 and AFG2 were ranged from 77.2% to 105.7% for coriander, chilli, cumin, curry mixture and soup mixtures; and from 63.6% to 90.1% for fennel, turmeric and kurma mixture. Recoveries for OTA ranged from 70.0% to 109.3% in coriander, chilli, cumin, fennel, turmeric and all spice mixtures. Acceptable recoveries are ranged from 70% to 110%. Relative standard deviation (RSD) for AFB1, AFB2, AFG1, AFG2 and OTA in all spices ranged from 3.18% to 10.81%. The method was validated using curry powder samples for selectivity, limit of detection (LOD), limit of quantification (LOQ),linearity and working range, accuracy (taken as recovery) and precision. The LOQ was found to be at 0.4μg/kg for AFB1/AFG1, 0.2μg/kg for AFB2/AFG2 and 0.5μg/kg for OTA respectively. The correlation coefficients of >0.99 have been obtained for all AFs and OTA. The accuracy and precision for this method were acceptable. The recoveries were between 77.7% to 88.1% for all analytes,meanwhile the precision were < 7.3% for repeatability and < 8.7% for reproducibility. This method was verified when 30 retails samples were analysed and 63.3% were found to contain AFs >LOQ, and 70.0% contained OTA >LOQ. The current results indicated potential of the extraction procedure to be used as a simultaneous determination for official food safety program and also for research purposes.